Frequency of Silent Cardiac Ischemia in Type II Diabetes Mellitus Patients - Tahir Angez Khan, Arshad Naeem, Muhammad Iqbal Qasim, Muhammad Arshad, Muhammad Sadiq, Huma Naeem Tareen, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: Finding out how often silent cardiac ischemia is in type II diabetic individuals was the aim of this investigation. Study Design: Descriptive/Cross-sectional Place and Duration: King Abdullah Teaching Hospital Mansehra during from April 2023 to September 2023. Methods: A total of 230 individuals with type II diabetes mellitus were included in this investigation. Following a comprehensive medical history assessment, the patient underwent electrocardiography (ECG) before to and subsequent to exercise tolerance testing. This was performed alongside the documentation of their height, blood pressure, weight, and fasting blood glucose levels (ETT). The EKG alterations were evaluated, and the patient was categorized as having silent cardiac ischemia based on the ECG findings. All data were analyzed using SPSS version 23.0. Results: The study comprised 150 males (65.2%) and 80 females (34.8%). The average age was 50.13 ± 11.34 years, with a mean BMI of 26.7 ± 8.44 kg/m². The mean fasting blood sugar level was 171 ± 22 mg/dl. The prevalence of hypertension was observed in 94 cases (40.9%), while 76 patients (33.04%) reported smoking status. A total of 100 cases (43.5%) were identified as having silent cardiac ischemia. A significant correlation was observed between silent cardiac ischemia and factors including advancing age, extended duration of diabetes mellitus, smoking history, hypertension history, and elevated body mass index (p-value 0.05). Conclusion: We made the observation that silent cardiac is fairly common in our community, which calls for prompt action to be taken in order to initiate the diagnosis of this problem at an early stage for the purpose of achieving better outcomes in the future. Keywords: Silent cardiac ischemia, Hypertension, Type II diabetes mellitus, BMI,